Splicing system in Automata Theory: A review - S. H., Khairuddin; Muhammad Azrin, Ahmad; Noraziah, Adzhar (IOP Publishing, 2019)
The study of formal language theory rapidly evolves after Tom Head introduce his research on formal language theory in 1987. Splicing system involves the process of cutting and pasting on DNA molecules with the presence of restriction enzymes and ligase, respectively. A mathematical model of the splicing system has been developed by using the concept of formal language theory, which is a branch of theoretical computer science and applied discrete mathematics, and informational macromolecules. Over the year, theoretical results in splicing systems have contributed to new research in formal language theory focused on modelling of biochemical processes. In this paper, the relation between formal language theory and some related molecular biological terms are explored. In addition, new ideas in the framework of biomolecular science, for example, the design of automated enzymatic processes are then discussed. Then, a mutual relation that exist in these field is then explained. The regular language can be implemented in the splicing system to show the DFA structure in the splicing system.